(untitled) (Fiep Bulletin - online, 2014)
Considered as one of the most important motor capacities, the reaction time represents the time interval enters the presentation of a stimulation and the beginning of the movement. Your measure it supplies a clarification of the internal processes that occur in the voluntary movement in diverse situations of day-by-day, in the learning of the movements, the sports and the rehabilitation. It can be simple, when, a stimulation will have only one possible reply and of choice when for different stimulations it has also different answers. For its peculiar characteristics the reaction time becomes a motor capacity of difficult evaluation, therefore it needs equipment that many times make it difficult the research as well as the evaluation in the sporting and school scope. Thus this research had for objective to create a test for evaluation of the times of simple reaction and choice of easy applicability and low cost, as well as carrying through analysis of reproductiveness of the same. After research was developed software through the tool Borland Delphi 7 that it uses the paschal programming language object. The software allow the fulfilment of the tests using itself of the two buttons of mouse. Through of visual stimulate generated is calculated the reaction time in accordance with the time that the evaluated one leads to answer. This test presented coefficients of reproductiveness of 0,805 for evaluation of the simple reaction time, and 0,838 for evaluation of choice reaction time, indices considered good for election of tests. The measure of the reaction time in the test is in milliseconds (ms). Thus, we consider that the test can in such a way be used in scientific research as in practical of the same training and in the school contributing for the work of the professionals and the researchers of the human movement.